Nitric oxide and physical exercise: modulations in physiological systems during elderly - Aguiar, Samuel da Silva; Ahmadi, Shirko; Silveira, Rodrigo; Prado, Raul Cosme Ramos do; Castro, Henrique de Oliveira; Asano, Ricardo Yukio; Asano, Ricardo Yukio; Coelho-Júnior, Hélio José (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Nitric oxide (NO) is a gaseous substance, which act as a key factor on the regulation of some physiological systems activity (e.g. cardiovascular, skeletal), since decrease on NO biodisponibility, such as on the pathway responsible for its production, lead to impairment on body homeostasis. Besides chronic pathological conditions, senescence — which is conceited as the healthy aging — NO levels and its pathway also can be found decreased. In front of this scenario, it is possible observe that there is necessity of therapies that act collaborating with the maintaining of a favorable environment to NO synthesis, as well to development of its functions during aging. Some trial has been observed in animals and in human beings the capacity of physical exercise to act collaborating to NO activity maintaining during senescence and senility. Objectives: To evaluate the effect of physical training on activity of pathway responsible for NO formation, as well as its blood concentrations in animal and elderly human models. Methods: A literature search was performed in the PubMed, Web of Science, Scielo and Lilacs databases, that evaluated the effects of physical training and nitric oxide formation in animal and elderly human models. Results: According to the studies reviewed in this research, pathway of the NO synthesis improves through physical exercise in animal and elderly human models. Conclusion: Scientific evidences demonstrate effectiveness of the physical exercise in inhibiting decrease of bioavailability in NO which accompanies senescence, greater magnitude and senility.